2016
DOI: 10.3892/br.2016.763
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of interferon-induced transmembrane protein-3 (IFITM3) rs7478728 and rs3888188 polymorphisms and the risk of pulmonary tuberculosis

Abstract: Abstract. The current study aimed to examine the possible association between the interferon-induced transmembrane protein-3 (IFITM3) gene polymorphisms and risk of pulmonary tuberculosis (PTB) in a sample population. This case-control study was conducted on 188 PTB patients and 169 healthy subjects. The rs7478728 and rs3888188 variants of IFITM3 were genotyped using polymerase chain reaction-restriction fragment length polymorphism. The findings showed no significant association between rs7478728 polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A subsequent study reported that the distribution of rs3888188 SNP in the IFITM3 gene correlated with the number of UC patients (Seo et al 2010;Wu et al 2007). Furthermore, rs3888188 SNP is associated Table 3 Linkage disequilibrium (LD) among fourteen polymorphisms in the chicken IFITM3 gene with the infection rate of tuberculosis and recent studies reported that the IFITM3 protein exhibited a broad spectrum of immune responses to variable pathogens, including not only enveloped viruses but also non-enveloped viruses and bacteria (Anafu et al 2013;Naderi et al 2016;Ranjbar et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent study reported that the distribution of rs3888188 SNP in the IFITM3 gene correlated with the number of UC patients (Seo et al 2010;Wu et al 2007). Furthermore, rs3888188 SNP is associated Table 3 Linkage disequilibrium (LD) among fourteen polymorphisms in the chicken IFITM3 gene with the infection rate of tuberculosis and recent studies reported that the IFITM3 protein exhibited a broad spectrum of immune responses to variable pathogens, including not only enveloped viruses but also non-enveloped viruses and bacteria (Anafu et al 2013;Naderi et al 2016;Ranjbar et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Variant rs3794624A/G of the CYBA gene that encodes p22phox, a subunit of the phagocyte nicotinamide adenine dinucleotide phosphate (NADPH) oxidase complex, was associated with susceptibility to TB in Han Chinese and Tibetan populations . SNP rs3888188G/T in the interferon‐induced transmembrane protein‐3 ( IFITM3 ) gene was associated with an increased risk of PTB in an Iranian population . SNP rs1052632A/G in the MR1 gene, which encodes a MHC class I‐related gene protein, was associated with the development of meningeal TB in Vietnamese patients.…”
Section: Candidate Gene Studies In Tuberculosismentioning
confidence: 99%